A “pretender” croconate-bridged macrocyclic tetraruthenium complex: Sizable redox potential splittings despite electronically insulated divinylphenylene diruthenium entities - Rotthowe, Nils; Linseis, Michael; Vogelsang, Lars; Orth, Nicole; Ivanovic-Burmazovic, Ivana; Winter, Rainer F. (Molecules, 2021)
Careful optimization of the reaction conditions provided access to the particularly small tetraruthenium macrocycle2 Ru2Ph-Croc, which is composed out of two redox-active divinylphenylene-bridged diruthenium entities Ru-1,4-CH=CH-C6H4-CH=CH-Ru (Ru2Ph; Ru = Ru(CO)Cl(PiPr3)2) and two likewise redox-active and potentially non-innocent croconate linkers. According to single X-ray diffraction analysis, the central cavity of2Ru2Ph-Croc is shielded by the bulky PiPr3 ligands, which come into close contact. Cyclic voltammetry revealed two pairs of split anodic waves in the weakly ion pairing CH2Cl2/NBu4BArF24 (BArF24 = [BC6H3(CF3)2-3,54]-electrolyte, while the third and fourth waves fall together in CH2Cl2 / NBu4PF6. The various oxidized forms were electrogenerated and scrutinized by IR and UV/Vis/NIR spectroscopy. This allowed us to assign the individual oxidations to the metal-organic Ru2Ph entities within2Ru2Ph-Croc, while the croconate ligands remain largely uninvolved. The lack of specific NIR bands that could be assigned to intervalence charge transfer (IVCT) in the mono-and trications indicates that these mixed-valent species are strictly charge-localized.2Ru2Ph-Croc is hence an exemplary case, where stepwise IR band shifts and quite sizable redox splittings between consecutive one-electron oxidations would, on first sight, point to electronic coupling, but are exclusively due to electrostatic and inductive effects. This makes2Ru2Ph-Croc a true “pretender”.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Crystal structure; Electrochemistry; Metallamacrocycle; Redox splitting; Spectroelectrochemistry